Brief Report: The Relationship Between Injection Drug Use Risk Behaviors and Markers of Immune Activation. (1st May 2017) - Deren, Sherry; Cleland, Charles M.; Lee, Haekyung; Mehandru, Saurabh; Markowitz, Martin
Abstract : Abstract: High levels of immune activation are reported for people who inject drugs. Studies of the relationship between injection behaviors and immune activation have yielded mixed results, in part due to lack of control for hepatitis C virus in analyses. This study, of 48 HIV-seronegative people who inject drugs, examines this relationship controlling for hepatitis C virus viremia. Frequency of injection was positively related to markers of immune activation (soluble CD14, %CD8 + CD38 + HLADR + T cells), as was duration of injection (high-specificity C-reactive protein and D-dimer). Sharing injection equipment was not related to markers studied. Findings suggest that efforts to encourage injection cessation or reduction in frequency can have positive health benefits through reducing immune activation.